2011
DOI: 10.1017/s000711451100417x
|View full text |Cite
|
Sign up to set email alerts
|

Body fat and fat-free mass measured by bioelectric impedance spectroscopy and dual-energy X-ray absorptiometry in obese and non-obese adults

Abstract: The aim of the present study was to compare body fat mass (FM) and fat-free mass (FFM) estimates by bioelectric impedance spectroscopy (BIS), with respective estimates by dual-energy X-ray absorptiometry (DXA), in obese and non-obese subjects. Body composition was measured in ninety-three obese and non-obese men and women by BIS device, BodyScout (Fresenius Kabi, Bad Homburg, Germany) and DXA device, Lunar iDXA (GE Healthcare, Madison, WI, USA). Mean difference between the methods was analysed by t tests, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…While the SF-BIA was found to significantly underestimate %BF relative to mean DXA outcomes, SF-BIA results were significantly correlated with HW (p < 0.05, r = 0.902), lending credence to their veracity. This outcome builds agreement with other projects investigating BCA in obese individuals; these researchers, which have previously warned that DXA and SF-BIA devices cannot be used interchangeably in light of the additive variability encompassed by these methods [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…While the SF-BIA was found to significantly underestimate %BF relative to mean DXA outcomes, SF-BIA results were significantly correlated with HW (p < 0.05, r = 0.902), lending credence to their veracity. This outcome builds agreement with other projects investigating BCA in obese individuals; these researchers, which have previously warned that DXA and SF-BIA devices cannot be used interchangeably in light of the additive variability encompassed by these methods [38][39][40].…”
Section: Discussionsupporting
confidence: 87%
“…BIS has also been reported to correlate better with FM than BMI and with visceral and/or intraabdominal fat (measured by MRI) than waist circumference or WHR . Overall, BIS has been reported to explain 80% to 90% of the variance in FM and visceral fat and 50% to 55% of the variance in intraabdominal fat by DXA and/or MRI . Despite the advantages of BIS, it has been reported to underestimate FM and overestimate FFM, especially in males , and BIS can be less reliable when the hydration status of FM and FFM are uncertain (e.g., in children, individuals with edema, and postbariatric surgery patients).…”
Section: Body Compositionmentioning
confidence: 99%
“…Overall, BIS has been reported to explain 80% to 90% of the variance in FM and visceral fat and 50% to 55% of the variance in intraabdominal fat by DXA and/or MRI . Despite the advantages of BIS, it has been reported to underestimate FM and overestimate FFM, especially in males , and BIS can be less reliable when the hydration status of FM and FFM are uncertain (e.g., in children, individuals with edema, and postbariatric surgery patients). In addition, there are multiple BIS systems available that have not been crossvalidated.…”
Section: Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was used by Lukaski et al 24) and Baumgartner et al 25) to estimate FFM and %FAT. Several studies revealed that FFM or %FAT could also be accurately predicted in various people using the BIA methods 26) . Additionally, with multi-frequency BIA, it is possible to estimate extracellular water and intracellular water compartments, along with TBW.…”
Section: Measurement Of Body Compositionmentioning
confidence: 99%